Expression of asporin reprograms cancer cells to acquire resistance to oxidative stress. Issue 3 (2nd February 2021) - Sasaki, Yuto; Takagane, Kurara; Konno, Takumi; Itoh, Go; Kuriyama, Sei; Yanagihara, Kazuyoshi; Yashiro, Masakazu; Yamada, Satoru; Murakami, Shinya; Tanaka, Masamitsu
Abstract: Asporin (ASPN), a small leucine‐rich proteoglycan expressed predominantly by cancer associated fibroblasts (CAFs), plays a pivotal role in tumor progression. ASPN is also expressed by some cancer cells, but its biological significance is unclear. Here, we investigated the effects of ASPN expression in gastric cancer cells. Overexpression of ASPN in 2 gastric cancer cell lines, HSC‐43 and 44As3, led to increased migration and invasion capacity, accompanied by induction of CD44 expression and activation of Rac1 and MMP9. ASPN expression increased resistance of HSC‐43 cells to oxidative stress by reducing the amount of mitochondrial reactive oxygen species. ASPN induced expression of the transcription factor HIF1α and upregulated lactate dehydrogenase A (LDHA) and PDH‐E1α, suggesting that ASPN reprograms HSC‐43 cells to undergo anaerobic glycolysis and suppresses ROS generation in mitochondria, which has been observed in another cell line HSC‐44PE. By contrast, 44As3 cells expressed high levels of HIF1α in response to oxidant stress and escaped apoptosis regardless of ASPN expression. Examination of xenografts in the gastric wall of ASPN –/– mice revealed that growth of HSC‐43 tumors with increased micro blood vessel density was significantly accelerated by ASPN; however, ASPN increased the invasion depth of both HSC‐43 and 44As3 tumors. These results suggest that ASPN has 2 distinct effects on cancer cells: HIF1α‐mediated resistance to oxidative stress via reprogramming of glucose metabolism, and activation of CD44‐Rac1 and MMP9 to promote cell migration and invasion. Therefore, ASPN may be a new therapeutic target in tumor fibroblasts and cancer cells in some gastric carcinomas. Abstract : We demonstrate the importance of ASPN‐mediated resistance of tumor cells to oxidative stress. ASPN expression increased the levels of HIF1a, which shifted glucose metabolism to anaerobic glycolysis and reduced the amount of mitochondrial reactive oxygen species (mtROS), thereby attenuating ROS‐induced apoptosis.